1998
DOI: 10.1007/bf03395287
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Classes Formation in Concurrent Discriminations in Rats as a Function of Overtraining

Abstract: The present two experiments conducted a limited parametric study of the overtraining variable using a whole-partial reversal procedure in rats. Rats received two concurrent two-choice discriminations (Experiment 1) , two concurrent go-no go successive discriminations (Experiment 2), and then received reversal training under a given condition of a whole reversal or a partial reversal either immediately after criterion training , following 2, 10, or 20 days of overtraining in Experiments 1 and 2. In Experiment 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
45
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(61 citation statements)
references
References 11 publications
15
45
0
1
Order By: Relevance
“…, 1992). The other is stimulus associations on a basis of the same response following the same consequence (Nakagawa, 1978(Nakagawa, , 1986(Nakagawa, , 1992(Nakagawa, , 1993(Nakagawa, , 1998Delius et aI., 1995). However, st imulus assoc iation mechanisms postulated by Nakagawa (1978Nakagawa ( , 1986Nakagawa ( , 1992Nakagawa ( , 1993Nakagawa ( , 1998 and Delius et al (1995) are not necessarily in conflict with stimulus association process based on downright reinforcement concordance (Edwards et aI., 1982;Hall et aI., 1993;Urcuioli et aI., 1989;Zentall, Sherburne, et aI., 1992, Zentall, Steirn, et aI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 1992). The other is stimulus associations on a basis of the same response following the same consequence (Nakagawa, 1978(Nakagawa, , 1986(Nakagawa, , 1992(Nakagawa, , 1993(Nakagawa, , 1998Delius et aI., 1995). However, st imulus assoc iation mechanisms postulated by Nakagawa (1978Nakagawa ( , 1986Nakagawa ( , 1992Nakagawa ( , 1993Nakagawa ( , 1998 and Delius et al (1995) are not necessarily in conflict with stimulus association process based on downright reinforcement concordance (Edwards et aI., 1982;Hall et aI., 1993;Urcuioli et aI., 1989;Zentall, Sherburne, et aI., 1992, Zentall, Steirn, et aI.…”
Section: Discussionmentioning
confidence: 99%
“…Group W learned their reversal faster than Group P after overtraining , but not after criterion training. These results indicate that the same response is a factor affecting stimulus classes formation in rats.There are two main views on the formation mechanism of stimulus classes: The one is categorization processes based on simple similarity between stimuli (Bhatt & Wasserman, 1989;Fersen & Lea, 1990; Vaughan & Herrstein, 1987), the other is stimulus associations on the basis of reinforcement concordance (Deli us, Ameling, Lea, & Staddon, 1995;Edwards, Jagielo, Zentall, & Hogan, 1982;Nakagawa, 1986Nakagawa, , 1992Nakagawa, , 1998 Urcuioli, Zentall, Jackson, Smith, & Steirn, 1989, 1998. However, it is important to note that such stimulus associations mechanism as postulated in Nakagawa (1986, 1992, 1998) and Delius et al (1995) is not necessarily in conflict with categorization processes based on simple similarity between stimuli.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding makes it clear that pigeons form stimulus classes. Nakagawa (1978Nakagawa ( , 1986Nakagawa ( , 1992Nakagawa ( , 1998, using a whole-partial reversal procedure which compared rats' performance on whole reversal sessions (both stimulus pairs reversed, from A+C-, 8+0-to A-C+, 8-0+ for example) with rats' performance on partial reversal sessions (only one pair reversed , from A-C+, 8-0+ to A+C-, 8-0+ for example) , reported that rats could form stimulus classes. In a series of Nakagawa's experiments, rats were trained to criterion or overtrained on two concurrent discriminations (A+C-, 8+0-) in both simultaneous (1986,1998) and go-no go successive concurrent discriminations (1992,1998) in Phase 1 training .…”
mentioning
confidence: 99%